Description of the female of Dicterias atrosanguinea Selys 1853, with notes on male genital ligula and male behavior (Odonata: Dicteriadidae) - Vilela, Diogo Silva; Guillermo-Ferreira, Rhainer; Cordero-Rivera, Adolfo (Zootaxa, 2018)
The female of Dicterias atrosanguinea Selys, 1853 is described and illustrated based on two specimens collected in Pará and Amazonas States, Brazil. We compare the female with the most closely related species, Heliocharis amazona Selys, 1853, and present SEM images of the genital ligula for both D. atrosanguinea and H. amazona males. Additionally we provide behavioral observations on D. atrosanguinea males.